식품가공 부산물 업사이클링을 위한 분리단백질의 이화학적 특성 - 홍은아(Eun Ah Hong); 송하영(Ha Young Song); 구민경(Min Kyung Gu); 정윤조(Yun Jo Jung); 조연재(Yeon Jae Jo); 김관수(Kwan Soo Kim); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2024)
본 연구는 곡류 및 유지작물 가공 부산물로부터 분리한 단백질의 이화학적 특성을 분석하였다. 분리 단백질의 조단백질 함량은 미강, 맥강, 밀기울, 대두박, 들깨박 및 참깨박에서 각각 74.72%, 74.35%, 86.84%, 82.07%, 85.52% 및 85.31 %로 미강 및 맥강이 낮은 함량을 나타내었다. 단백질 회수율은 들깨박에서 77.85%로 가장 높았으며, 밀기울에서 44.17 %로 가장 낮았다. 총 필수아미노산 함량은 100 mg당 30.51 ~39.48 mg 범위였으며, arginine과 methionine은 참깨박 분리단백질에서 각각 11.13 및 2.94 mg/100 mg으로 높았고, lysine은 대두박 분리단백질에서 7.08 mg/100 mg으로 가장 높았다. 유지흡수력은 참깨박 분리단백질에서 408.96 %로 가장 높았고, 대두박에서 180.32%로 낮았다. 용해도는 25.97(참깨박)~93.14(대두박)% 범위였다. 이상의 결과를 종합해 보면 식품가공 부산물로부터 분리된 단백질 중 참깨박 단백질과 대두박 단백질을 조합하면 아미노산 밸런스를 보완하여 우수한 단백질원으로 활용될 수 있을 것으로 판단된다. This study evaluated the physicochemical properties of proteins isolated from the processing of by-products of cereal and oilseed crops. The crude protein content of the isolated proteins was 74.72%, 74.35%, 86.84%, 82.07%, 85.52%, and 85.31% for rice bran, barley bran, wheat bran, soybean meal, perilla meal, and sesame meal, respectively. The protein recovery rate was the highest at 77.85% in perilla meal and the lowest at 44.17% in wheat bran. The total essential amino acid content ranged from 30.51 to 39.48 mg/100 mg, with arginine and methionine being the highest in sesame meal protein at 11.13 and 2.94 mg/100 mg, respectively, and lysine the highest in soybean meal protein at 7.08 mg/100 mg. The oil absorption capacity was the highest at 408.96% in sesame meal protein, and the lowest at 180.32% in soybean meal protein. Solubility ranged from 25.97% (sesame meal) to 93.14% (soybean meal). Based on the above results, the combination of sesame meal protein and soybean meal protein, both isolated from food processing by-products, can be utilized as an excellent protein source that complements the amino acid balance. KCI Citation Count: 0